2016
DOI: 10.1097/bot.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Contribution of Tension-Reducing Rotator Cuff Sutures in 3-Part Proximal Humerus Fractures

Abstract: Tension-relieving rotator cuff sutures do not add stability to the repair of 3-part proximal humerus fractures. Varus collapse and greater tuberosity displacement are common complications associated with 3-part fractures. No mechanical data exist to demonstrate benefit of adding suture to a plate and screw construct for limiting fracture displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…We have learned important predictors of success include restoration or maintenance of the medial calcar [43], avoiding varus alignment [44], and less aggressive proximal screw fixation [45]. Although not biomechanically shown to be beneficial, rotator cuff sutures have become the standard among fracture surgeons for fragment mobilization, provisional reduction, and final construct incorporation [46]. More recent analyses of proximal humerus fractures treated with newer locking plates show less complications and improved outcomes.…”
Section: Orif With Locked Platesmentioning
confidence: 99%
“…We have learned important predictors of success include restoration or maintenance of the medial calcar [43], avoiding varus alignment [44], and less aggressive proximal screw fixation [45]. Although not biomechanically shown to be beneficial, rotator cuff sutures have become the standard among fracture surgeons for fragment mobilization, provisional reduction, and final construct incorporation [46]. More recent analyses of proximal humerus fractures treated with newer locking plates show less complications and improved outcomes.…”
Section: Orif With Locked Platesmentioning
confidence: 99%
“…Arvesen et al performed a cadaveric study and concluded that tension-relieving rotator cuff sutures with no. 5 FiberWire do not add stability to the repair of 3-part proximal humeral fractures [25]. Furthermore, Voigt et al also reported no contribution to reduce interfragmentary motion by additive fiber-cerclages in unstable 3-part fracture model with an intact rotator cuff [26].…”
Section: Discussionmentioning
confidence: 99%
“…This low sampling rate prevents conclusion with certainty that the long posterior screws decrease the strength of spine and/or lead to fracture at lower loads. However, other biomechanical studies have utilized six specimens per group [13][14][15][16]. Specimen number 13 in the L2 (superior screw "all inside, " posterior screw outside-in) group failed at higher load than specimen numbers 10 and 12, which had both screws with outside-in fixation into the scapular spine.…”
Section: B Amentioning
confidence: 99%